2005
DOI: 10.1002/dvdy.20631
|View full text |Cite
|
Sign up to set email alerts
|

Pea3 expression is regulated by FGF signaling in developing retina

Abstract: FGF signaling has been implicated as an important regulator of retinal development. As a first step in characterizing potential downstream targets of FGF signaling in the retina, we have analyzed expression of Pea3, a member of the Pea3 class of Ets-domain transcription factors, in the developing eye. We find that Pea3 is expressed in the developing retina, and its transcription is regulated by FGF receptor activation. In addition, FGF signaling activates Cath5, a gene necessary for retinal ganglion cell diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 72 publications
3
29
1
Order By: Relevance
“…To our knowledge, this is one of very few studies of regulation of ETV genes by FGFs in mammals; Hasewaga et al demonstrated that FGF18 stimulated expression of ETV1, ETV4, and ETV5 in the mouse embryonic brain (Hasegawa et al, 2004). It has been stated that ETV4 is regulated by FGF in all (lower vertebrate) tissues studied (McCabe et al, 2006), but the present study suggests that this may only hold for non-mammalian vertebrates.…”
Section: Journal Of Cellular Physiologycontrasting
confidence: 45%
“…To our knowledge, this is one of very few studies of regulation of ETV genes by FGFs in mammals; Hasewaga et al demonstrated that FGF18 stimulated expression of ETV1, ETV4, and ETV5 in the mouse embryonic brain (Hasegawa et al, 2004). It has been stated that ETV4 is regulated by FGF in all (lower vertebrate) tissues studied (McCabe et al, 2006), but the present study suggests that this may only hold for non-mammalian vertebrates.…”
Section: Journal Of Cellular Physiologycontrasting
confidence: 45%
“…This pattern continued at E10.5 (data not shown). Moreover, frontonasal expression of Spry1 and Pea3 , two Fgf8 -responsive genes (Brent and Tabin, 2004; Firnberg and Neubuser, 2002; McCabe et al, 2006; Minowanda et al, 1999; Roehl and Nusslein-Volhard, 2001), was highly reduced or lost by E10.5 in Fgf8 null/Neo embryos (Figure 4b, c). …”
Section: Resultsmentioning
confidence: 92%
“…FGF signaling may cooperate with Shh to coordinate the subsequent spread of RGC differentiation wave front. FGF19, via regulation of the Pea3 and Erm Ets-domain transcription factor genes, together with Shh released from new born RGCs, are required for propagation of Shh own gene expression (McCabe et al, 2006;Vinothkumar et al, 2008). Mutations in Shh signaling components and cyclopamine treatment all disrupt normal propagation of Shh and Atoh7 expression as well as RGC differentiation (Neumann and Nuesslein-Volhard, 2000;Stenkamp and Frey, 2003).…”
Section: Extrinsic Signalingmentioning
confidence: 99%